Passing Off Dalam Persaingan Usaha Yang Menimbulkan Pelanggaran Hak Atas Merek - Aliyya, Annisa Lisaana Sidqin; Dirkareshza, Rianda (Jurnal Ilmiah Penegakan Hukum, 2023)
This paper aims to find out the Passing Off activities that was carried out on service trading brands in the form of Banks owned by State-Owned Enterprises (BUMN), namely PT Bank Mandiri (Persero) Tbk and the impacts it caused. The problem is focused on actions in business competition that occur when an irresponsible party takes advantage of a brand that already has a reputation and is well-known that belongs to another party by carrying out piggybacking and/or pillaging which is known as Passing Off. To approach this problem, a normative type of legal research is used, which then collects data through references from laws and regulations and is complemented by interviews. This study concludes that there is a company called PT Pengelola Investama Mandiri which has had an impact in the form of misinterpretation for the public and/or consumers because it has taken the Passing Off action by owning and using a logo identical to PT Bank Mandiri (Persero) Tbk for approximately 4 (four) years, while they are not part of or affiliated with the company.